Genetic Loci Associated With COVID-19 Positivity and Hospitalization in White, Black, and Hispanic Veterans of the VA Million Veteran Program - Peloso, Gina M.; Tcheandjieu, Catherine; McGeary, John E.; Posner, Daniel C.; Ho, Yuk-Lam; Zhou, Jin J.; Hilliard, Austin T.; Joseph, Jacob; O’Donnell, Christopher J.; Efird, Jimmy T.; Crawford, Dana C.; Wu, Wen-Chih; et al. (Frontiers in Genetics, 2022)
SARS-CoV-2 has caused symptomatic COVID-19 and widespread death across the globe. We sought to determine genetic variants that contribute to COVID-19 susceptibility and hospitalization in a large biobank linked to a national U.S. health system. We identified 19,168 (3.7%) lab-confirmed COVID-19 cases among Million Veteran Program participants between March 1, 2020 and February 2, 2021 including 11,778 Whites, 4,893 Blacks, and 2,497 Hispanics. A multi-population genome-wide association study (GWAS) for COVID-19 outcomes identified four independent genetic variants (rs8176719, rs73062389, rs60870724, and rs73910904) contributing to COVID-19 positivity including one novel locus found exclusively among Hispanics. We replicated eight of nine previously reported genetic associations at an alpha of 0.05 in at least one population-specific or the multi-population meta-analysis for one of the four MVP COVID-19 outcomes. We used rs8176719 and three additional variants to accurately infer ABO blood types. We found A, AB, and B blood types were each associated with testing positive for COVID-19 compared with O blood type with the risk being highest for the A blood group. We did not observe any genome-wide significant associations for COVID-19 severity of outcomes among those testing positive. Our study replicates prior GWAS findings associated with testing positive for COVID-19 among mostly White samples and extends findings at three loci to Black and Hispanic individuals. We also report a new locus among Hispanics requiring further investigation. These findings may aid in the identification of novel therapeutic agents to decrease the morbidity and mortality of COVID-19 across all major ancestral populations.